Pengaruh Pengelolaan dan Status Sosial Ekonomi Orang Tua Terhadap Perilaku Konsumtif Mahasiswa IAIN Langsa - Zulfa Eliza; Zikriatul ulya; Nanda Syafriani (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of the influence of financial management and parents' socio-economic status either partially or simultaneously on the consumptive behavior of IAIN Langsa students. The independent variables studied were Financial Management and Parents' Socio-Economic Status. The dependent variable studied is Consumptive Behavior. This research is a quantitative research. The type of data used in this study is primary data. The data analysis methods in this study were in the form of data quality tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis testing. Financial management is positively related to consumptive behavior, from the results of the study it was found that Financial Management had a positive and significant effect on Consumptive Behavior with a contribution of 11,074 tcount > ttable (11,074 > 1,972). So the hypothesis H01 is rejected. The socioeconomic status of parents is positively related to consumptive behavior. From the results of the study, it was found that the Socio-Economic Status of Parents had a significant and significant effect on consumptive behavior with the contribution of the influence of (3.600 > 1.972). So the hypothesis H02 is rejected. Financial Management and Parents' Socio-Economic Status have a significant effect on consumptive behavior with a simultaneous hypothesis test obtained by the value of Fcount > Ftable (143.819 > 3.04). The author's suggestion for IAIN Langsa students is that they are expected to be able to control themselves from impulsive purchases, students are expected not to be easily captivated by the discounts offered or easily influenced by friends, trends or influencer. be a wise student in determining purchases and be able to distinguish between wants and needs to avoid consumptive behavior.